2018
DOI: 10.1002/14651858.cd012551.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for treating chronic prostatitis/chronic pelvic pain syndrome

Abstract: Some of the interventions can decrease prostatitis symptoms in an appreciable number without a greater incidence of adverse events. The QoE was mostly low. Future clinical trials should include a full report of their methods including adequate masking, consistent assessment of all patient-important outcomes including potential treatment-related adverse events and appropriate sample sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 143 publications
0
26
0
2
Order By: Relevance
“…Cognitive behavioural therapy (CBT) is useful for psychosocial effects and phosphodiesterase-5 inhibitors (for example, sildenafil) are recommended for sexual dysfunction. Finally, a recent Cochrane review (Franco et al, 2018) showed that acupuncture has been shown to reduce symptoms compared with standard medical therapy.…”
Section: Managementmentioning
confidence: 99%
“…Cognitive behavioural therapy (CBT) is useful for psychosocial effects and phosphodiesterase-5 inhibitors (for example, sildenafil) are recommended for sexual dysfunction. Finally, a recent Cochrane review (Franco et al, 2018) showed that acupuncture has been shown to reduce symptoms compared with standard medical therapy.…”
Section: Managementmentioning
confidence: 99%
“…Over the last six decades, CP/CPPS, attributed to infection, inflammation, impaired urothelial integrity and function, endocrine imbalance, autoimmunity, voiding dysfunction, or neuropsychological factors [7,8], has remained a 'diagnosis of exclusion' with currently unclear or inexact underlying cause, thus stimulating interest and concerted research effort to demystify its etiology and unravel probable underlying molecular mechanisms. Recently, Trichomonas Vaginalis infection has been suggested as a probable pathoetiologic factor in CP/CPPS because of its complicity in chronic persistent prostatic infection and prostate epithelial cell inflammation [9].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of effect and the disproportional mean decrease in the NIH Chronic Prostatitis Symptom Index (NIH-CPSI) and response rates in treatment groups in comparison to placebo groups suggest the superiority of directed multi-modal therapy over monotherapy, and advocate consideration of these agents for optimal management of patients with CP/CPPS [17]. Alternatively, phytotherapies, including quercetin, Cernilton, Eviprostat/pollen extract, and pentosane polysulfate [17,18], as well as non-pharmacological therapies such as acupuncture and extracorporeal shockwave therapy (ESWT), have also shown some efficacy in the treatment of CP/CPPS [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In particular, in a recent Cochrane systematic review exploring the efficacy and safety of the available nonpharmacological CP/CPPS treatments, low-intensity shockwave therapy (LiST) emerged as a novel, promising treatment modality that improves pain and other CP/CPPS symptoms without presenting serious adverse events. 7 Despite these encouraging findings, to date, LiST has failed to derive sufficient guideline recommendations supporting its application as a part of the CP/CPPS treatment algorithm. 8,9 The latter was attributed to the high heterogeneity in terms of LiST duration, frequency and number of sessions, as well as to the different shockwave generators and energy setting applied across the available randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%